The Marine Strategy Framework Directive: monitoring of Mediterranean circalittoral and bathyal coral reefs - Angiolillo, Michela; Giusti, Michela; Bo, Marzia; Enrichetti, Francesco; Toma, Margerita; Rende, Sante Francesco; Rossi, Lorenzo; Izzi, Alessia; Pazzini, Alfredo; Tunesi, Leonardo (Biologia Marina Mediterranea, 2025)
Habitat-forming species are known worldwide to play a key role in structuring benthic ecosystems and enhancing biodiversity and ecosystem functioning. In deep waters, habitat-forming corals (i.e., stony corals, black corals, and gorgonians) can form bioconstructions or dense assemblages known as coral reefs and gardens, threatened by several stressors. In the Mediterranean Sea, considerable effort has been made over the past two decades to unveil the distribution, extent, and ecological role of these habitats. However, quantitative data on their conservation status still need to be improved. Under the European Marine Strategy Framework Directive (MSFD), monitoring activities have been carried out in Italian waters since 2020 (every three years) to fill these gaps. The aim is to assess the ecological status of coral forests and scleractinian cold-water reefs using diversity, health status, and impact variables. Monitoring was conducted using remotely operated vehicle technologies between 100 and 650 m depth in nine areas and 90 sites of the three MFSD subregions bordering Italy. The results of the first monitoring cycle are presented, and biodiversity hotspots are identified. The investigated habitats showed different health conditions, ranging from almost pristine, as in the Corsica Channel, to severely stressed by marine litter and fishing-related items, as in the Dohrn Canyon. No extensive habitat destruction was observed. Differences in species composition and abundance among the investigated areas were highlighted, showing the peculiarity of each area, the associated megafauna, the exclusive species, and the population status. These monitoring activities increase knowledge of key benthic and vulnerable species and habitats, providing a preliminary baseline assessment of distribution, population structure and conservation status with respect to the main sources of impact. This information is pivotal for assessing the effectiveness of the measures implemented by the MSFD and evaluating the need for additional specific conservation initiatives.